IMPLEMENTASI SISTEM INFORMASI ADMINISTRASI BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL (STUDI KASUS : TOKO NUANSA WANGI) - Husodo, Purwani; karismayanti, Siti; Bagus Wahyu Pandhito; Dwi Sosanto (Sekolah Tinggi Ilmu Komputer El Rahma, 2026)
Accelerating digitalization in the Micro, Small, and Medium Enterprises (MSMEs) sector is a major urgency in maintaining business resilience in the era of industry 4.0, but many traditional retail businesses still face data management constraints due to conventional administrative systems. This research and community service activity aims to transform operational governance at Toko Nuansa Wangi Bogor through the implementation of a website-based Administrative Information System. The main problems identified include inefficiency in inventory recording, the risk of financial data redundancy, and the difficulty of real-time transaction monitoring. The system development method uses the Rapid Application Development (RAD) approach with Unified Modeling Language (UML) modeling. The system is built using the Laravel framework with a Model-View-Controller (MVC) architecture to ensure scalability and data security. The results show that the implementation of this system successfully increased the efficiency of administrative data processing by 85% and provided automatic inventory accuracy. A significant impact achieved is the creation of more transparent, systematic, and accountable business governance for store managers in making data-driven business decisions.